Avaliação do uso de inibidores de tirosina quinase em pacientes com leucemia mielóide crônica - Goulart, Valéria Pereira (2016)
Chronic myeloid leukemia (CML) results from the clonal proliferation of a hematopoietic stem cell representing approximately 15-20% of all cases of leukemia. It is characterized by the presence of the Philadelphia chromosome (Ph), which is the result of the reciprocal translocation between chromosomes 9 and 22. The molecular consequence of translocation is the formation of a hybrid gene, BCR-ABL, encoding a chimeric protein with an intense and dysregulated tyrosine kinase activity, thereby, providing the phenotype of the disease. Over the years, there have been several therapeutic landmarks in the treatment of CML, from busulfan and hydroxyurea until the advent of allogeneic Hematopoietic Stem Cell Transplantation (HSCT) and alpha-interferon. Imatinib mesylate, the first selective tyrosine kinase inhibitor, has been approved by regulatory authorities in 2001 and since that revolutionized the treatment of CML, producing the best therapeutic effects already achieved, except for the HSCT. The excellent clinical results with this drug turned it into the treatment of choice for newly diagnosed patients. Tyrosine kinase second generation inhibitors, such as nilotinib and dasatinib, have been developed having a higher power in order to decrease the chance of disease resistance and expand treatment further options. Presently these drugs are more specific and effective because they are able to trigger a response to the hematological, cytogenetic and molecular level, allowing the patient to have an overall survival practically equal to the general population as well as a quality of life. This cohort study does a retrospective by analyzing medical records of patients with CML treated with tyrosine kinase inhibitors at the University Hospital of Santa Maria (UHSM), attended by the Unified Health System (UHS), describes the epidemiology of this disease in the institution, its evolution in terms of hematologic responses, cytogenetic and molecular, overall survival (OS), progression-free survival (PFS), event-free survival (EFS) and more frequent adverse effects. 98 patients were included, 88.8% in chronic phase, with a mean age of 47.36 years and 58.2% of them were men. About the adverse effects, the most frequent ones were the cramp, myalgia rash and 20%, 15%, 14% respectively. Twelve patients had additional cytogenetic changes to the Ph chromosome, and 50% of these changes were related to worsening of the disease. The HCR was achieved by 91.88%, 84% and 58.33% of patients using imatinib, Dasatinib and Nilotinib respectively. Molecular response was obtained by 78.55% of patients treated with Imatinib, 72% with Dasatinib and 58.7% with Nilotinib. The probability of OS was 95% for 60 months, while PFS and EFS, in the same period, was 85.4% and 69.4% respectively. Patients treated with tyrosine kinase inhibitors in HUSM showed a high frequency of hematological and molecular responses, PFS and OS similar to those described in the world's literature, justifying the investment made by SUS in the purchase of this product.